Análise da eficiência técnica das cooperativas de crédito brasileira: um estudo dos sistemas Sicoob e Sicredi - Mateus Rocha Menezes (2014)
Financial institutions are important to the economic development of society, so that these institutions must be properly structured in operational spheres, administrative and financial, with operations guided by efficiency, compliance with legal aspects and socioeconomic demands. Brazilian credit unions are nonprofit financial institutions are being encouraged to expand the sector by government agencies. The search for its financial services has increased significantly, therefore, these certain organizations must operate efficiently in order to meet these demands. In this sense, the present study aimed to evaluate the technical efficiency of Brazilian credit unions affiliated to SICOOB and SICREDI systems. The methodology used to measure the technical efficiency of these financial institutions was the Data Envelopment Analysis (DEA) through the classical model BCC - Banker, Charnes and Cooper (1984), which assumes variable returns to scale, orientation was chosen to output. The implemented input-output matrix, based on the definition of efficiency in credit unions, has as inputs the Capital, the Funding Expenses, the Notes Expenses Borrowings and Transfers, Administrative Expenses and Other Operating expenses, and how outputs the Loans and the Surplus. Through this methodology were measured technical efficiency indexes for each cooperative sample System1, an average of 262 units, and sample System 2 with at least 35 cooperatives on average for the years 2007 until 2013. How many years were used to measure the efficacy of the sample of credit unions, we calculated the rate of change of total factor product ivity with purpose to identify the occurrence of progress or return in efficiency indicator sover the year sand what factors contributed to change productivity. This index is known in the DEA literature as Malmquist index, using the model proposed by Rayand Desli (1997). The results, the measure is the efficiency index for sample studied credit unions, were satisfactory, identifying the sample System1an average technical efficiency index above 80%, especially in the years 2009, 2010, 2011 and 2012, and the years 2007, 2008 and 2013 had average indices close to 80% efficiency. The System 1 cooperatives units operating with technical efficiency are on average 29% of the sample. Sample System 2 on average, had a rough technical efficiency to 95% for the years 2008 to 2013, highlighting the efficiencies 2010 and 2011 with 99%, while the 2007 year of the sample held an average of technical efficiency of 88%. Al ready units System 2 operating with technical efficiency are on average 70% of the sample for the years 2007 to 2013, the years 2010 and 2011 stood holding their 90% and 87% of the amount of efficient credit unions. The results of the Malmquist index, measured for sample of System 1, indicated progress through to technological changes for the years 2011 to 2013 and with the highest percentage of contribution by changes in technical efficiency from 2007 to 2012, however, the rate of change the scale efficiency of the factors indicated return over the periods 2007 to 2008 and from 2009 to 2011, and shall the System 1 cooperatives seek gains in scale efficiency. While, the System 2 cooperatives stopped progress in the average index of Malmquist, with a greater contribution to technological change and technical efficiency change.